Dietary patterns of early childhood and maternal socioeconomic status in a unique prospective sample from a randomized controlled trial of Prenatal DHA Supplementation. Issue 1 (December 2016) - Hidaka, Brandon; Kerling, Elizabeth; Thodosoff, Jocelynn; Sullivan, Debra; Colombo, John; Carlson, Susan
Abstract Background Dietary habits established in early childhood and maternal socioeconomic status (SES) are important, complex, interrelated factors that influence a child's growth and development. The aim of this study was to define the major dietary patterns in a cohort of young US children, construct a maternal SES index, and evaluate their associations. Methods The diets of 190 children from a randomized, controlled trial of prenatal supplementation of docosahexaenoic acid (DHA) were recorded at 6-mo intervals from 2-4.5 years by 24-h dietary recall. Hierarchical cluster analysis of age-adjusted, average daily intake of 24 food and beverage groups was used to categorize diet. Unrotated factor analysis generated an SES score from maternal race, ethnicity, age, education, and neighborhood income. Results We identified two major dietary patterns: "Prudent" and "Western." The 85 (45%) children with a Prudent diet consumed more whole grains, fruit, yogurt and low-fat milk, green and non-starchy vegetables, and nuts and seeds. Conversely, those with a Western diet had greater intake of red meat, discretionary fat and condiments, sweet beverages, refined grains, French fries and potato chips, eggs, starchy vegetables, processed meats, chicken and seafood, and whole-fat milk. Compared to a Western diet, a Prudent diet was associated with one standard deviation higher maternal SES (95% CI: 0.80 to 1.30). Conclusions We found two major dietary patterns of young US children and defined a single, continuous axis of maternal SES that differed strongly between groups. This is an important first step to investigate how child diet, SES, and prenatal DHA supplementation interact to influence health outcomes. Trial registration NCT00266825 . Prospectively registered on December 15, 2005